Temporary food handlers’ compliance with effective food-hygiene practices - Saad, Mazni; See, Toh Poh; Adil, Mohamed Azam Mohamed (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2018)
Success in food handling depends, in part, on a self-regulation practice factor that accounts for better results in food safety. A self-report study conducted on 318 food handlers reveal that temporary workers were able to comply with the overall hygiene practices outlined in the 1983 Malaysian Food Act and the 2009 Food Hygiene Regulations. This study also shows that proper training of these workers could result in high-level hygiene practices at public food service institutions that would satisfy the community’s appetite for safe and healthy food.